Pengembangan Bahan Ajar Bahasa Arab Berbasis Model Pembelajaran SAVI untuk Meningkatkan Keterampilan Bahasa Arab Siswa Kelas X di MAN 3 Jombang - Sukmawati, Sayepti Dwi; Hidayah, Nurul; Shofiyani, Amrini (YASIN, 2025)
Arabic language learning at MAN 3 Jombang continues to face challenges, including low student participation, lack of enthusiasm, and difficulty in understanding the material due to monotonous and minimally interactive teaching resources. This study aims to: (1) develop Arabic instructional materials based on the SAVI (Somatic, Auditory, Visual, Intellectual) learning model to enhance students' language skills; (2) evaluate the effectiveness of the materials; and (3) assess their feasibility. The method used is Research and Development (R&D) with the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The research subjects were 40 tenth-grade students of class X-13 at MAN 3 Jombang. Data were obtained through pretest–posttest scores, expert validations (content and media), and student response questionnaires. The validation results indicated a feasibility score of 88.3% from content experts, 92.7% from media experts, and 87.1% from student responses. Normality testing confirmed that the data were normally distributed, and the paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. The study concludes that Arabic teaching materials based on the SAVI model are both feasible and effective, capable of enhancing language skills, encouraging active participation, and creating a more engaging and interactive learning environment. The findings imply that developing instructional materials grounded in somatic, affective, visual, and intellectual approaches can serve as an innovative strategy for Arabic language instruction.